Good refugees, bad migrants? Intergroup helping orientations towards refugees, migrants and economic migrants in Germany - Wyszynski, M. (2020)
The present study examined the effect of group labels on helping behavioral intentions toward displaced people in Germany. Specifically, it examined the impact of different labels evoking either voluntary or forced migration (i.e., migrants, economic migrants, and refugees) on different helping orientations (e.g., dependency vs. autonomy-ori-ented helping) and if these effects occur via perceived intergroup threat, warmth and competence stereotypes. Participants (N = 304) were randomly assigned to one of three conditions (refugee vs. migrant vs. economic migrant) and read fabricated case vignettes, featuring a displaced person who arrived in Germany recently. Results showed that, as predicted, the use of different group labels affected the helping ori-entations of host society members, as well as, the stereotypes they held. No signifi-cant label effects were found for intergroup threat. While the label refugee evoked dependency-oriented helping intentions and triggered paternalistic stereotypes, the label economic migrants increased opposition to help, decreased help affirmation and evoked envious stereotypes. Practical implications to strengthen peaceful intergroup relations between host society members and newcomers are discussed.